Properties of Soils Irrigated by Saline Waters in Arid Tracts of Western Rajasthan - Shankaranarayana, H. S.; Ganu, S. N. (Journal of Soil and Water Conservation, 2022)
Underground waters of western Rajasthan are generally saline. Shankaranarayana et al (1962) made a detailed study of consider- able number of waters from Jodh- pur and Pali districts of Rajasthan and concluded that the waters of the region are very high in sodium chloride followed by sodium sulphate with very high salinity and sodium hazard. The problem of employing saline waters is a soil problem as it involves in the impoverishment of the soil in course of time. Accumu- lation of the salts and solonetziflca- tion of the soils are important as- pects of the problem that ensue as a result of irrigation with saline waters, UNESCO (1956). Puffeles (1939) has remarked that the ques- tion of emDlovment of brakish water for irrigation is a problem for the soil scientist and agricultural scien- tist rather than directly for a bio- logist as vegetation is tolerant of degrees of salinity higher than those which involve the impoverishment of the soil in course of time. Never- theless it is important for the area to utilize these saline waters for ir- rigation due to the lack of other sources and irrigation is in progress in a large measure for decades in the region.